MOTIVASI SISWA TERHADAP MATA PELAJARAN SENI BUDAYA (MUSIK) KELAS X DI SMK MUHAMMADIYAH 1 PADANG - Deta Oktaviani Putri; Irdhan Epria Darma Putra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to analyze students’ learning motivation toward the Cultural Arts (Music) subject at SMK Muhammadiyah 1 Padang. The type of this study is qualitative research, with data collection methods including observation, interviews, documentation, and literature review, and data analysis through collection, identification, classification, clarification, and description. The results generally indicate that intrinsic motivation arises through feelings of joy, pride, and personal satisfaction when successfully playing a song, while extrinsic motivation is driven by positive feedback, competition, and rewards, which mutually reinforce each other, ultimately forming a genuine interest in Minangkabau traditional music.